Hustle Culture as a Contemporary Form of Idolatry: A Theological Analysis of the Old Testament - Ferry Sonny Lumintang; Ramli Sarimbangun (Riviera Publishing, 2026)
The hustle culture phenomenon in modern society reflects a significant shift in life orientation, where success and productivity become the primary sources of identity and meaning. Therefore, this study aims to analyze hustle culture as a form of contemporary idolatry from the perspective of Old Testament theology and affirm its relevance to today's faith life. This research is important because it provides a critical theological framework for reading modern social phenomena that are often considered neutral but actually contain profound spiritual implications. The method used is a qualitative approach through the study of literature with theological-biblical analysis of key texts, especially Exodus 20:3 and Deuteronomy 8:17–18, and supported by contemporary theological literature. The main argument of this study states that hustle culture is a form of modern idolatry that is non-material, where success and career function as